Circulating miRNA-486 as a novel diagnostic biomarker for right ventricular remodeling - Cai, Huiling; Yu, Cheng; Li, Xiuchuan; Wang, Xuenan; Yang, Yongjian; Lan, Cong (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveClinical practice currently faces a significant shortfall in specific biomarkers needed for diagnosing right ventricular (RV) remodeling in patients with pulmonary hypertension (PH). While small noncoding microRNAs (miRNAs) are crucial regulators of RV remodeling, the biomarker potential of serum miRNAs in this process is little known. This study systematically screened and identified candidate serum miRNAs as potential diagnostic biomarkers for RV remodeling in PH patients.MethodsPulmonary artery banding (PAB) was performed in Sprague-Dawley (SD) rats and RV modeling was measured by echocardiographic and histological analyses 4 weeks after surgery. High-throughput miRNA sequencing of serum samples was performed to profile differentially-expressed miRNAs (dif-miRNAs) and preliminarily screen candidate miRNAs. The diagnostic power of the candidate miRNA was further validated in 100 patients [20 with adaptive RV pressure overload; 20 with maladaptive RV pressure overload; 20 with left heart failure (LHF); 19 with left ventricular hypertrophy and 21 controls].ResultsPAB rats exhibited severe RV hypertrophy, fibrosis and enlargement of RV cardiomyocytes compared with sham group. MiRNA sequencing analyses revealed 19 dif-miRNAs (12 upregulated and 7 downregulated) between the two groups. Among the 12 upregulated miRNAs, miRNA-486 exhibited highest elevation in PAB group and was supposed to be the candidate biomarker for RV modeling. Serum miRNA-486 levels were lower in control and left ventricular hypertrophy (LVH) patients compared to PH patients, and significantly higher in maladapted RV patients than in adapted RV patients. Serum miRNA-486 was significantly higher in LHF patients compared to controls, but still significantly lower than in PH patients. In receiver operating characteristic (ROC) analysis, serum miRNA-486 was a good predictor of RV maladaptation in PH patients (cut-off value 3.441, AUC 0.8625), which was not significantly different from B-type natriuretic peptide (BNP). Elevated serum miRNA-486 levels (≥3.441) were associated with reduced TAPSE/PASP ratios and increased BNP levels.ConclusionsSerum miRNA-486 has the potential to be a valuable noninvasive biomarker for diagnosing RV remodeling in patients with PH.